Analysis of The Legal Strength of Land Tenure Statement (SPPT) as a Basis for Land Rights in East Kutai Regency, East Kalimantan Province - Badrunsyah, Badrunsyah; Barthos, Megawati (Jurnal Indonesia Sosial Sains, 2024)
Research on the legal strength of land tenure statements (SPPT) as a basis for land rights in East Kutai Regency, East Kalimantan, aims to find out the position of the SPPT as proof of land rights in the land law system and the legal strength of a land tenure statement as proof of ownership rights. Above ground. This research was carried out because many landowners in East Kutai still rely on the legality of their land using SPPT as proof of land ownership. They assume that having the SPPT is strong enough as proof of ownership of land rights. This can be seen in the number of land cases that enter the judicial process where the SPPT is still recognized. Meanwhile, based on the negative land law system with a positive tendency adopted by Indonesia, the strongest evidence for land ownership rights is only a certificate issued by the National Land Agency, and even then it still has the potential to be sued as long as the truth can be proven. In this research, normative and descriptive juridical research methods are used to answer legal issues by describing, analyzing, assessing, and explaining appropriately and analyzing applicable laws and regulations as well as various opinions of legal experts, with the aim of answering the problems raised.